Adsorption of TDS and chloride ions from partially treated tannery wastewater using activated coffee husk - Nazrawit Debebe Tadess; Getasew Yehuala Gezahegn; Yosef Hagos Abrha (Discover Materials)
Abstract The aim of this study was to treat tannery wastewater by using activated carbon derived from coffee husk to effectively remove total dissolved solids (TDS) and chloride ions. The tannery’s wastewater discharged to the environment is often untreated or partially treated. Due to the current worldwide water shortage, it is essential to develop sustainable strategies for managing water resources, such as recycling and reusing after treatment. Therefore, finding cost-effective and eco-friendly methods to purify contaminated water is crucial. In the study, activated coffee husk has been found to be effective for removing TDS and chloride ions from tannery wastewater. Activated coffee husk was evaluated by conducting experiments with chemical activation using phosphoric acid. The carbonized coffee husk was then used to remove total dissolved solids (TDS) and chloride ions from tannery wastewater. To investigate the adsorption process of TDS and chloride ions on the activated coffee husk surface, contact time (1–3 h), pH (5–9), and adsorbent dosage (1–3 g/L) were considered. The activated coffee husk was characterized using SEM (Scanning Electron Microscopy), FTIR (Fourier Transform Infrared Spectroscopy), BET (Brunauer Emmett Teller), and XRD (X-ray diffraction). The adsorption isotherm and kinetics were determined using different models. Design expert was used to optimize TDS and chloride ions adsorption and the optimal conditions were 2.38 h of contact time, pH of 7.19, and 2.54 g/L adsorbent dosage. The removal efficiency of 77.88% for chloride ions and 72.73% for TDS indicates a higher efficacy compared to traditional methods using commercial activated carbon. The Langmuir isothermal model of R2 value for both TDS and chloride ions were 0.9969 and 0.9504 respectively. The adsorption kinetics of TDS and chloride ions follow a pseudo-second-order model, indicating that chemisorption is the rate-limiting step in the process.